2018
DOI: 10.1002/adma.201805188
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Large‐Area 2D Polycrystalline Transition Metal Carbides for Hydrogen Electrocatalysis

Abstract: hydrogen evolution using sustainably produced electricity has promised a carbonfree production of a chemical fuel. [5] However, most commercial hydrogen is still produced via steam reforming of methane because there are few scalable base-metal replacements for platinum at the scales required for electrocatalysis. [6] Dimensional reduction of 3D materials to 0D, 1D, or 2D nanostructures (thickness vs lateral size < 1%), [7,8] has attracted interest for discovering intriguing new catalytic properties. Notably, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 59 publications
0
58
0
2
Order By: Relevance
“…MXene is a new type of 2D materials that have attracted great interest due to its unique properties and great potential for use in different energy storage devices . However, because of the random restacking of the MXene nanosheets (NSs) there is a loss of accessible surface area and an increase of ion diffusion resistance that greatly lower their electrochemical performance.…”
mentioning
confidence: 99%
“…MXene is a new type of 2D materials that have attracted great interest due to its unique properties and great potential for use in different energy storage devices . However, because of the random restacking of the MXene nanosheets (NSs) there is a loss of accessible surface area and an increase of ion diffusion resistance that greatly lower their electrochemical performance.…”
mentioning
confidence: 99%
“…[28] The transparency of a logo pattern induced on the PI film and then transferred to the WPU substrate is shown in Figure 1b, which also indicates the convenience and universality of our stretchable MSC fabrication method. [40,41] More importantly, the high-magnification image in Figure 1e reveals that LIG is decorated evenly with small round convex particles, indicating a portion of the hybrid NiO/Co 3 O 4 nanoparticles were distributed on surface. [12,15] While in situ synthesized NiO/Co 3 O 4 /LIG shows a completely different morphology (Figure 1d) in that the entire structure is composed of multilayer graphene, which is a synergistic result of the simultaneous carbonization of PI and gelatin.…”
Section: Morphology and Structure Analysismentioning
confidence: 98%
“…[37] Second, stretchable MSCs assembled on PDMS and silicone rubber, which cannot be degraded under natural conditions, pose a potential threat to the living environment. [40][41][42] It was found that the gelatin could modify the surface morphology and wettability of NiO/ Co 3 O 4 /LIG. [39] In this work, a gelatin-mediated ink containing Ni and Co ions was coated onto a PI film and subjected to laser direct writing, during which the gelatin was completely cocarbonized with PI while in situ synthesizing laser-induced graphene/NiO/ Co 3 O 4 (NiO/Co 3 O 4 /LIG).…”
mentioning
confidence: 99%
“…Neutral electrolytes could result in high operation voltages as compared with those in acidic and alkaline electrolytes by reducing the possibility of inducing the water hydrolysis reaction due to either the hydrogen evolution reaction (HER) or oxygen evolution reaction (OER) ,,. Furthermore, materials with low absorption energy of hydrogen or oxygen are generally good catalysts for HER and OER . Meanwhile, materials with poor catalytic efficiency such as carbon‐based materials have high overpotentials.…”
Section: Electrode‐aqueous Electrolyte Systems With High Working Voltagementioning
confidence: 99%